Effectiveness of Problem-Based Learning to Improve Critical Thinking Ability of Chemistry Students on Acid-Base Material - Jusniar; Syamsidah; Sakinah, Zubair; Munthalib; Sentot, Kusairi (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine the improvement of critical thinking skills of chemistry students through a problem-based learning (PBL) learning model on acid-base titration material. The method used is analytical descriptive research based on categorizing critical thinking skills with the research subject of chemistry education students in a regular class in 2022, consisting of 35 students. Data collection of critical thinking skills using essay tests reveals critical thinking skills in interpretation, analysis, inference, deduction, and evaluation. Research data were obtained from pretest and post-test results. The results showed the lowest N-gain value on the interpretation indicator and the highest on the deduction indicator, with an average N-gain value of 0.59 in the moderate category. This shows increased critical thinking skills after being treated using the PBL learning model.